In-situ FTIR spectroscopy of epoxy resin degradation: kinetics and mechanisms - Pannico, Marianna; Mensitieri, Giuseppe; Musto, Pellegrino (Frontiers in Chemistry, 2024)
In the present contribution, we report on an in-situ FTIR study of the thermo-oxidative degradation of a flexible epoxy resin. Different and complementary approaches to the analysis of the spectral data were employed, which provided a detailed description of the process in terms of kinetics and mechanisms. A preliminary Normal Coordinate Analysis, based on the DFT method, allowed for a reliable interpretation of the observed spectrum, increasing the amount of available structural information. Two-dimensional correlation spectroscopy provided details on the evolution of the reacting network structure. The relative stability of the various functional groups was ranked and the most likely sites of initiation were identified. Oxygen fixation on the network chains produced amide and ketone groups, with the latter developing at a higher rate. The kinetic profiles of various functional groups were accurately simulated by a first-order, biexponential model, which afforded a quantitative comparison among their relative stabilities. The spectroscopic analysis allowed us to propose likely mechanisms and to identify those that occur preferentially.